ANALYSIS OF INVENTORY MANAGEMENT AT PT LAKSANA ABADI MANDIRI - Adlina Bunyamin, Sabrina
PT Laksana Abadi Mandiri is one of the distributors of medical equipment in Bandung, Indonesia. One of the problems it is facing is inventory management regarding understocking and overstocking. The company is not using any method for their inventory managamenet. This research aims to find the most cost-effective inventory control methodology in this company by comparing two widely known approaches: Economic Order Quantity and Just-In-Time. It will also be explaining the most accurate methods of demand forecasting to help the company improve its inventory management.